Taklik Talak as a Form of Reforming Islamic Family Law in Indonesia - Sulfianti Irma Pai'pinan; Rameyza Elya Yulianti; Kurniati Kurniati (al-Rasῑkh: Jurnal Hukum Islam, 2026)
In the context of family law in Indonesia, taklik talak (divorce by mutual consent) is a legal reform that aims to protect the rights of wives and address the imbalances that often occur in divorce cases. However, the effectiveness of this instrument is often hindered by low legal literacy and cultural stigmas that perceive taklik talak as a mere formality or even an "ill omen" at the beginning of a marriage. This study aims to analyze taklik talak as a legal reform instrument and evaluate the sociological barriers that prevent its optimal implementation. Using a juridical-normative approach through literature study and critical synthesis of various journals and legislation (including the Compilation of Islamic Law), this research yields three main findings. First, taklik talak is a written legal innovation that serves as a dual protection tool with a preventive function (daf’ al-mafāsid). Second, this instrument effectively realizes gender justice by ensuring the fulfillment of the wife's financial rights as regulated in Article 149 of the KHI. Third, the optimization of the public interest (maṣlaḥah) in taklik talak is still hampered by sociological challenges, such as taboo views in society that trigger a gap between progressive regulations and field reality. The conclusion indicates that sociological intervention through in-depth education is required to shift public perception so that taklik talak is understood as a family risk management tool to protect women's dignity.